2008
DOI: 10.1016/s1473-3099(08)70254-8
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbicides and the prevention of HIV transmission

Abstract: Worldwide, nearly half of all individuals living with HIV are now women, who acquire the virus largely by heterosexual exposure. With an HIV vaccine likely to be years away, topical microbicide formulations applied vaginally or rectally are being investigated as another strategy for HIV prevention. A review of preclinical and clinical research on the development of microbicides formulated to prevent vaginal HIV transmission yielded 118 studies: 73 preclinical and 45 clinical. Preclinical research included in-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
131
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 147 publications
0
131
0
4
Order By: Relevance
“…The availability of a safe, inexpensive, and effective microbicide would have the potential to help stop the spread of HIV (9,30). Animal models are critical to the development, testing, and implementation of novel and effective microbicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of a safe, inexpensive, and effective microbicide would have the potential to help stop the spread of HIV (9,30). Animal models are critical to the development, testing, and implementation of novel and effective microbicides.…”
Section: Discussionmentioning
confidence: 99%
“…currently undergoing large-scale clinical trials for efficacy in HIV prevention (7,9). One of these trials, the Center for the AIDS Program of Research in South Africa (CAPRISA) 004, recently reported that 1% tenofovir gel can partially prevent vaginal HIV transmission (1).…”
mentioning
confidence: 99%
“…Development of an effective vaccine or microbicide offers the greatest hope for protection for this vulnerable group. Recent setbacks in both fields, however, suggest that mucosal protection may be harder to achieve than previously anticipated (8,14,20,33).…”
mentioning
confidence: 96%
“…Sodium lauryl sulfate (SLS) is an anionic surfactant and has recently been tested as novel microbicidal agent that demonstrated signiicant lethal activity against a broad spectrum of STD pathogens, including HIV-1 [102]. This agent behaves as a liquid at room temperature and converts into gel form at body temperature to protect the STI transmission [103,104]. Therefore it can be used as invisible condoms.…”
Section: Sodium Lauryl Sulfatementioning
confidence: 99%